A Comparison of Fresenius Com.Tec Cell and Spectra Optia Cell Separators for Autologous and Allogeneic Stem Cell Collections: Single Center Experience - Solmaz, Serife; Kahraman, Selda; Sevindik, Omur Gokmen; Acar, Celal; Turkyilmaz, Munire; Alacacioglu, Inci; Demirkan, Fatih (Springer India, 2018)
Peripheral blood is the prefered source for hematopoietic stem cells for hematopoietic stem cell transplantation. The efficiency of peripheral blood stem cell (PBSC) collection can vary among devices. In this study we aimed to compare feasibility and effectivity of apheresis procedures of the different systems. Two apheresis systems [Com.Tec (Fresenius Healthcare) and Spectra Optia (Caridian BCT)] were used in our center for the collection of PBSCs for autologous and allogeneic transplantation. We retrospectively analysed 190 apheresis procedures performed in healthy donors and patients between June 2012 and November 2014 in Department of Hematology, Dokuz Eylul University. PBSCS were collected by Fresenius cell separator (64 procedure) or Spectra Optia cell separator (126 procedure). Mobilization treatments were G-CSF (26.8%), cyclophosphamide plus G-CSF (48.4%), prelixafor plus G-CSF (14.7%), ESHAP (10%) and others. Patient and donor characteristics (age, weight, volume processed, disease, mobilization regimes) were similar in Fresenius and Spectra Optia apheresis groups. Altough both collected PBSCs efficiently, the amount of CD34+ cell in product collected by Spectra Optia device was significantly higher (p<0.05) and product volume was lower than Fresenius Com.Tec significantly (p<0.05). CD34+ collection efficiency with Spectra Optia was significantly higher than Fresenius Com.Tec (CE2: 87%, 70%, p=0.033) regarding all procedures. High collection efficiency and low product volume may be a significant characteristic of Spectra Optia device (mean 187mL, product CD34+ cell: 1576 mu L).
Keywords: Apheresis; Peripheral blood stem cell; Autologous transplantation; Allogeneic transplantation; Blood cell seperators